The Principal’s Managerial Role in Implementing the Excellent Hafidz Program at Islamic Elementary School - Poncowati, Tutik; Yuliejantiningsih , Yovitha; Soedjono, Soedjono (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study examines the principal’s managerial role in implementing the Hafidz Excellence Program at MI Raudlatul Muta’allimin Pakis, Bringin District, Semarang Regency. The research was motivated by the need to develop an effective management model for Qur’an memorization programs that simultaneously strengthen students’ character and spiritual values. The study aims to analyze how the principal carries out the four managerial functions—planning, organizing, implementing, and supervising—in managing the program to improve students’ competence in Qur’an memorization and discipline. A qualitative descriptive approach with a case study design was employed. Data were collected through interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, display, and conclusion drawing. The findings reveal that the principal effectively performs all managerial functions by involving teachers and parents in participatory planning, structuring clear task divisions, motivating students through rewards and guidance, and ensuring program quality through systematic supervision and evaluation. This comprehensive managerial approach fosters collaboration, consistency, and accountability among stakeholders, thereby improving student performance and spiritual growth. The study implies that effective principal management integrating modern leadership principles with Islamic values can serve as a sustainable model for faith-based educational institutions seeking to enhance Qur’anic learning and character education.